Protective effects for HLA-B*40:01 and C*03:04 in NPM1-mutated AML: result of a large HLA association study - Rücker-Braun, Elke; Falk, Bose; Baldauf, Henning; Massalski, Carolin; Schäfer, Gesine; Altmann, Heidi; Sauter, Jürgen; Solloch, Ute V.; Lange, Vinzenz; Egger-Heidrich, Katharina; Kunadt, Desiree; Stölzel, Friedrich; et al. (Frontiers in Immunology, 2025)
IntroductionMutations in the nucleophosmin 1 gene (NPM1) are common and recurrent molecular abnormalities in acute myeloid leukemia (AML). NPM1 mutations are considered to be positive prognostic factors. The beneficial effect may be due to immune responses mediated by cytotoxic T cells targeting HLA-presented peptides derived from mutated NPM1 and thereby suppressing mutated NPM1-positive hematopoiesis. While the immunogenicity of these NPM1 peptides has not been demonstrated conclusively, certain HLA-types have been linked to a lower risk of NPM1-mutated AML. MethodIn a comprehensive HLA association study at two-field resolution, we compared the proportions of HLA class I alleles between NPM1-mutated (n = 477) and/or DNMT3A-mutated (n = 216) patients with AML and a control group of healthy individuals (n = 51,890). ResultWe found HLA-B*40:01 and HLA-C*03:04 to be significantly underrepresented in NPM1-mutated AML compared to the control group (4.0% vs. 10.2%, p < 0.001, and 8.2% vs, 15.9%, p < 0.001, respectively). This might suggest that neoepitopes presented by these HLA alleles trigger T-cell responses. Online epitope prediction tools predict that mutated NPM1-derived peptides bind strongly to B*40:01 and C*03:04. DiscussionBased on these findings, further studies should confirm the presence and functionality of neoepitope-specific T cells and characterize specific T-cell receptors (TCR). Sequence information might eventually be exploited in immunotherapeutic approaches to treat AML patients with TCR-engineered T cells or bispecific TCR T/NK cell engagers.